Atelectasis in obese patients undergoing laparoscopic bariatric surgery are not increased upon discharge from Post Anesthesia Care Unit - Braun, Matthias; Ruscher, Lea; Fuchs, Alexander; Kämpfer, Martina; Huber, Markus; Luedi, Markus M.; Riva, Thomas; Vogt, Andreas; Riedel, Thomas (Frontiers in Medicine, 2023)
Background Obese patients frequently develop pulmonary atelectasis upon general anesthesia. The risk is increased during laparoscopic surgery. This prospective, observational single-center study evaluated atelectasis dynamics using Electric Impedance Tomography (EIT) in patients undergoing laparoscopic bariatric surgery. Methods We included adult patients with ASA physical status I–IV and a BMI of ≥40. Exclusion criteria were known severe pulmonary hypertension, home oxygen therapy, heart failure, and recent pulmonary infections. The primary outcome was the proportion of poorly ventilated lung regions (low tidal variation areas) and the global inhomogeneity (GI) index assessed by EIT before discharge from the Post Anesthesia Care Unit compared to these same measures prior to initiation of anesthesia. Results The median (IQR) proportion of low tidal variation areas at the different analysis points were T1 10.8% [3.6–15.1%] and T5 10.3% [2.6–18.9%], and the mean difference was −0.7% (95% CI: −5.8% −4.5%), i.e., lower than the predefined non-inferiority margin of 5% (p = 0.022). There were no changes at the four additional time points compared to T1 or postoperative pulmonary complications during the 14 days following the procedure. Conclusion We found that obese patients undergoing laparoscopic bariatric surgery do not leave the Post Anesthesia Care Unit with increased low tidal variation areas compared to the preoperative period.